BIOACCUMULATION OF TRACE METALS BY MARINE FLORA AND FAUNA NEAR A CAUSTIC SODA PLANT (KARWAR, INDIA) - Krishnakumar, P K; Pillai, V K; Valsala, K K (Indian Journal of Fisheries, 2011)
The concenlration of Cd, Pb, Cu, Zn and Mn in fishes, shell fishes and seaweed near a caustic soda plant has been measured. Trace metal concentration in the oyster (Crassostrea cucullata), mussel (Pema viridis) and seaweed (Sargassum tenerimum) collected from the vicinity of discharge point were found to be comparatively high. It is found that oysters are more effective bioaccumulators for Zn, Cu, and Cd, whUe mussels and seaweeds for Pb and Mn. There were no significant differences between the whole soft tissue for Pb and Cd concentration of P. viridis collected from a relatively clean and contaminated sites. The kidney and mantle showed significant differences for all the trace metals, gill for Zn, Cu, Pb and Cd and digestive gland for Zn, Cu and Cd. The kidney was found to be a major site of trace metal accumulation followed by digestive gland, from both the sites.